2006
DOI: 10.1083/jcb.200606145
|View full text |Cite
|
Sign up to set email alerts
|

Human SHPRH suppresses genomic instability through proliferating cell nuclear antigen polyubiquitination

Abstract: Differential modifications of proliferating cell nuclear antigen (PCNA) determine DNA repair pathways at stalled replication forks. In yeast, PCNA monoubiquitination by the ubiquitin ligase (E3) yRad18 promotes translesion synthesis (TLS), whereas the lysine-63–linked polyubiquitination of PCNA by yRad5 (E3) promotes the error-free mode of bypass. The yRad5-dependent pathway is important to prevent genomic instability during replication, although its exact molecular mechanism is poorly understood. This mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
178
3
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(188 citation statements)
references
References 23 publications
4
178
3
3
Order By: Relevance
“…On the other hand, SHPRH has an H1 and H5 linker sequence and a PHD domain not present in either Rad5 or HLTF. Because SHPRH can also promote the polyubiquitination of PCNA (12,13), it will be important to examine the overlaps and differences between the functions of HLTF and SHPRH, suggested by their domain structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, SHPRH has an H1 and H5 linker sequence and a PHD domain not present in either Rad5 or HLTF. Because SHPRH can also promote the polyubiquitination of PCNA (12,13), it will be important to examine the overlaps and differences between the functions of HLTF and SHPRH, suggested by their domain structures.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we and others have shown that human SHPRH, which resembles Rad5 in having a SWI/SNF helicase domain and a C 3 HC 4 RING motif, exhibits a ubiquitin ligase activity able to promote PCNA polyubiquitination in a Rad6-Rad18-and Mms2-Ubc13-dependent manner (12,13).…”
mentioning
confidence: 94%
“…SHPRH directly interacts with PCNA, RAD18, and UBC13, but not with RAD6 (9). To examine whether HLTF has similar binding properties, 3XFLAG-HLTF-containing cell extract was incubated with GST-fused PCNA, UBC13, or RAD6 ( Fig.…”
Section: Physical Interactions Between Hltf and Proteins Participatinmentioning
confidence: 99%
“…Despite the presence of UBC13 and MMS2 homologues in humans, the importance of the TS pathway is less clear in mammals because K63-linked polyubiquitination of PCNA, a hallmark event for the TS pathway, had not been observed until recently (8)(9)(10). We recently identified human SHPRH, which possesses SWI2/SNF2 and RING domains with similar architecture to the yeast Rad5 as a functional homologue of yeast Rad5 (9). Specifically, we demonstrated the in vivo activity of SHPRH in promoting a K63-linked polyubiquitination of PCNA as well as physical interactions of SHPRH with PCNA, RAD18, and UBC13.…”
mentioning
confidence: 99%
“…Regardless of the mode of reaction, it is abundantly clear that the error-free DDT process is highly conserved in the entire eukaryotic kingdom, from yeast to human. Sequence and functional homologs of all proteins involved in error-free DDT, including Mms2 [140], Ubc13 [141] and Rad5 [142,143], have been found in mammals, plants and other higher eukaryotes [144,145]. For a few limited examples, suppression of the above genes resulted in phenotypes reminiscent of the corresponding yeast mutants [143,146,147].…”
Section: Error-free Ddtmentioning
confidence: 99%